Use of Expert and/or Expert Report in Penal Trial or Administrative Action: Cabibs 1395; 1527; 1574; 1578 and 1579 - Jorgensen, Gerald T. (CLSA advisory opinions, 2001-2005, 2001)
Does canon law require that in the psychological evaluation of a priest, only a forensic evaluation or an evaluation using forensic protocols may be employed?